American Policy of Pre-emptive War: Motives and Legal Legitimacy - ABDELLAOUI, Ouafa; BOUSBIA LAICHE, Maissa (جامعة الوادي - University of Eloued, 2023)
تتتبع هذه الدراسة تاريخ السياسات والاستراتيجيات الدفاعية الأمريكية ، كجزء من السياسة الخارجية الأمريكية ، في ضوء فحص العقائد الدفاعية المختلفة لرؤساء الولايات المتحدة. تركز هذه الدراسة على سياسة جورج بوش الابن الدفاعية. أحد العناصر المهمة في استراتيجية بوش الدفاعية هو استخدام الحرب الوقائية للدفاع عن المصالح القومية للولايات المتحدة ، ودعم حلفاء الولايات المتحدة ، ومعاقبة أعداء الولايات المتحدة الحقيقيين والمحتملين. يؤكد هذا البحث أن أي دولة لها الحق في الدفاع عن أراضيها ومصالحها بكل الوسائل المشروعة والقانونية. لكن الدراسة تشكك أيضًا في شرعية وقانونية استخدام الضربات الاستباقية لتحييد الأخطار والأعداء الذين يهددون أمن أمريكا والأمريكيين. من أجل الرد على الإشكالية المذكورة سابقًا ، تهدف هذه الدراسة إلى التحقق من الدوافع وراء استخدام الحروب الوقائية كاستراتيجية دفاعية بشكل رئيسي خلال فترة الرئيس جورج بوش الابن. كما تحاول ردم الهوة بين ما هو عسكري بحت وما هو قانوني في جوهره ، للتحقق من شرعية هذه الأعمال العسكرية التي يتبناها صناع القرار السياسي والعسكري الأمريكيين في مناطق الحرب المختلفة ، وخاصة في أفغانستان والعراق. هذه الدراسة نوعية حيث يتم استخدام المنهج الوصفي التحليلي لجمع البيانات وتحليلها وتفسيرها كمناهج بحث في القسم النظري من الدراسة ، كما تمت مراجعة وتحليل وتفسير البيانات المختلفة ذات الصلة باستراتيجية الدفاع الأمريكية والحرب الاستباقية. بعد ذلك ، تم تقييم استراتيجية الدفاع ، الحرب الوقائية ، من حيث توافقها أو انتهاكها للقانون الدولي والإنسان. كشفت نتائج الدراسة أن الضربات الاستباقية تعد انتهاكًا للقوانين الدولية وأبسط الحقوق الإنسانية لضحايا هذه الأعمال العسكرية. This study traces the history of the American defense policies and strategies. In United States foreign policy, in the light of examining different presidents` defense doctrines. The study focuses on George W. Bush defense policy. A significant element in Bush defense strategy is the utilization of the preemptive war to defend the national interests. This research work asserts that any country has the right to defend its territories with all legitimate and legal means. However, the study also questions the legitimacy and legality of using pre-emptive strikes to neutralize dangers and enemies threatening the security of America . this study aims to investigate the motives behind using preemptive wars as a defense strategy during Bush administration. It attempts to bridge the gap between what is purely military and what is legal in essence, to check the legitimacy of these military actions adopted by the political and military decision-makers, mainly in Afghanistan and Iraq. This study is qualitative where the descriptive- analytical approach to data gathering, analyzing, and interpreting are used as research methods. In the theoretical section of the study, various data relevant to the United states defense strategy and preemptive war were reviewed, analyzed, and interpreted. Then, the defense issue, preemptive war, was evaluated for its violation to the international and humanitarian law(s) and legislation(s). The findings revealed that the preemptive strikes conducted by the United States were a violation of the international laws and the simplest humanitarian rights for the victims of these military actions.
Master’s Degree in Literature and Civilization
Keywords: Defense strategy, George W. Bush, Motives, Legitimacy, Preemptive war; استراتيجية الدفاع ، جورج بوش ، الدوافع ، الشرعية ، الحرب الوقائية